Infection with the entomopathogenic nematodes Steinernema alters the Drosophila melanogaster larval microbiome - Raymond Yau; Christina Pavloudi; Yingying Zeng; Jimmy Saw; Ioannis Eleftherianos (PLoS ONE, 2025)
The fruit fly Drosophila melanogaster is a vital model for studying the microbiome due to the availability of genetic resources and procedures. To understand better the importance of microbial composition in shaping immune modulation, we can investigate the role of the microbiota through parasitic infection. For this, we use entomopathogenic nematodes (EPN) of the genus Steinernema which exhibit remarkable ability to efficiently infect a diverse array of insect species, facilitated by the mutualistic bacteria Xenorhabdus found within their gut. To examine the microbiome changes in D. melanogaster larvae in response to Steinernema nematode infection, D. melanogaster late second to early third instar larvae were exposed separately to S. carpocapsae and S. hermaphroditum infective juveniles. We have found that S. carpocapsae infective juveniles are more pathogenic to D. melanogaster larvae compared to the closely related S. hermaphroditum. Our microbiome analysis also indicates substantial changes in the size and composition of the D. melanogaster larval microbiome during infection with either nematode species compared to the uninfected controls. Our results serve as a foundation for future studies to elucidate the entomopathogenic-specific effector molecules that alter the D. melanogaster microbiome and understand the role of the microbiome in regulating insect anti-nematode immune processes.